Martyrologium Romanum Gregorii XII (1872)
Keywords: 1.Conservation 保護; 10.Cover Damage; 18.Bookworm; 2.Damage

Romanorum, Pontificum Epistolae Selectae (Libraria Academica Wagneriana, 1872)
Stamp
Keywords: 1.Conservation 保護; 2.Damage

Romanorum Pontificum Innocentii, Zosimi, Bonifacii et Coelestini (Libraria Academica Wagneriana, 1872)
Stamp
Keywords: 1.Conservation 保護; 15.Stain 污漬; 2.Damage

Sancti Gregorii Papae I (apud. P. Lethielleux, 1872)
Stamp
Keywords: 1.Conservation 保護; 15.Stain 污漬; 2.Damage

Sancti Gregorii Papae I (apud. P. Lethielleux, 1872)
Stamp
Keywords: 1.Conservation 保護; 15.Stain 污漬; 2.Damage

Yarndale: an Unsensational Story (Longmans, Green, and Co, 1872)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 18.Bookworm

Historia da Egreja Catholica em Portugal - Amado, Jose de Sousa (na Typographia De G. M. Martins, 1872)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 10.Cover Damage; 18.Bookworm; 2.Damage

Obras completas de Platón - D. Patricio de Azcárate (mMedina Y Navarro., 1872)
Keywords: 10.Cover Damage; 18.Bookworm (Only Cover); 2.Damage; Condition: Fair; Hard Cover; Philosophy

Obras completas de Platón - D. Patricio de Azcárate (mMedina Y Navarro., 1872)
Keywords: 10.Cover Damage; 18.Bookworm (Only Cover); 2.Damage; Condition: Fair; Hard Cover; Philosophy

Obras completas de Platón - D. Patricio de Azcárate (mMedina Y Navarro., 1872)
Keywords: 10.Cover Damage; 18.Bookworm (Only Cover); 2.Damage; Condition: Fair; Hard Cover; Philosophy

Tertulliani, Apologeticum - Florentis, Q. Sept. (apud P. Lethielleux, 1872)
Stamp
Keywords: 1.Conservation 保護; 15.Stain 污漬; 2.Damage

Diccionario portuguez-latino: impresso por ordem d'el-rei fidelissimo o senhor dom José I ... para uso das escolas de todos os reinos e senhorios de Portugal - Fonseca, Pedro José da (Bertrand, 1872)
Signature
Keywords: 10.Cover Damage; 18.Bookworm; 2.Damage; 22.signature; Condition: Fair; Dictionaries; Multilingual dictionaries; Portuguese language; Portuguese language Dictionaries Latin; languages

Diccionario portuguez-latino: impresso por ordem d'el-rei fidelissimo o senhor dom José I ... para uso das escolas de todos os reinos e senhorios de Portugal - Fonseca, Pedro José da (Bertrand, 1872)
Signature
Keywords: 10.Cover Damage; 18.Bookworm; 2.Damage; 22.signature; Condition: Fair; Dictionaries; Multilingual dictionaries; Portuguese language; Portuguese language Dictionaries Latin

Diccionario portuguez-latino: impresso por ordem d'el-rei fidelissimo o senhor dom José I ... para uso das escolas de todos os reinos e senhorios de Portugal - Fonseca, Pedro José da (Bertrand, 1872)
Keywords: 10.Cover Damage; 18.Bookworm; 2.Damage; Condition: Fair; Dictionaries; Multilingual dictionaries; Portuguese language; Portuguese language Dictionaries Latin

Diccionario portuguez-latino: impresso por ordem d'el-rei fidelissimo o senhor dom José I ... para uso das escolas de todos os reinos e senhorios de Portugal - Fonseca, Pedro José da (Bertrand, 1872)
Keywords: 10.Cover Damage; 18.Bookworm; 2.Damage; Condition: Fair; Dictionaries; Multilingual dictionaries; Portuguese language; Portuguese language Dictionaries Latin

Defeza do Christianismo ou Conferencias Sobre A Religiao - Frayssinous, Monsenhor D. (Em Casa de A. R. da Cruz Coutinho, 1872)
Stamp of Saint Joseph Seminary
Keywords: 1.Conservation 保護; 10.Cover Damage; 18.Bookworm; 2.Damage

A Eupropa Em 1848 ou Consideracoes Sobre A Organisacao do Trabalho - Gaume, J (F. J. V. de Carvalho, Editor, 1872)
Keywords: 1.Conservation 保護; 2.Damage

The Odes and Epodes of Horace - Horace; Lytton, Edward Bulwer Lytton (Longmans, Green, and Co., 1872)
OCLC: 9882045
Keywords: 10; 18.Bookworm; 2.Damage; Condition: Fair; Hard Cover; Horace; Horace Translations into English; Laudatory poetry; Latin; Laudatory poetry; Latin Translations into English; Translations

F. C. R. Billuart, Summa Sancti Thomae - J. B. J. Lequette (Apud Victorem Palme, Bibliopolam, 1872)
Keywords: 1.Conservation 保護; 10.Cover Damage; 18.Bookworm; 2.Damage

F. C. R. Billuart, Summa Sancti Thomae - J. B. J. Lequette (Apud Victorem Palme, Bibliopolam, 1872)
Keywords: 1.Conservation 保護; 10.Cover Damage; 18.Bookworm; 2.Damage

F. C. R. Billuart, Summa Sancti Thomae - J. B. J. Lequette (Apud Victorem Palme, Bibliopolam, 1872)
Keywords: 1.Conservation 保護; 10.Cover Damage; 18.Bookworm; 2.Damage

F. C. R. Billuart, Summa Sancti Thomae - J. B. J. Lequette (Apud Victorem Palme, Bibliopolam, 1872)
Keywords: 1.Conservation 保護; 10.Cover Damage; 18.Bookworm; 2.Damage

F. C. R. Billuart, Summa Sancti Thomae - J. B. J. Lequette (Apud Victorem Palme, Bibliopolam, 1872)
Keywords: 1.Conservation 保護; 10.Cover Damage; 18.Bookworm; 2.Damage

F. C. R. Billuart, Summa Sancti Thomae - J. B. J. Lequette (Apud Victorem Palme, Bibliopolam, 1872)
Keywords: 1.Conservation 保護; 10.Cover Damage; 18.Bookworm; 2.Damage

F. C. R. Billuart, Summa Sancti Thomae - J. B. J. Lequette (Apud Victorem Palme, Bibliopolam, 1872)
Keywords: 1.Conservation 保護; 10.Cover Damage; 18.Bookworm; 2.Damage

Historia da Egreja Catholica em Portugal - José de Sousa Amado (Typographia de G.M. Martins, 1872)
Keywords: 18.Bookworm; Condition: Fair; Hard Cover; History

Bullarium Parronatus Portugalliae Regum In ecclesiis, Africae, Asiae Atque Oceaniae - Manso, Vicecomite de Paiva (Ex Typographia Nationali, 1872)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 18.Bookworm

Bullarium Parronatus Portugalliae Regum In ecclesiis, Africae, Asiae Atque Oceaniae - Manso, Vicecomite de Paiva (Ex Typographia Nationali, 1872)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 18.Bookworm

Onde Estamos? - Mer. Gaume (96- Largo dos Clerigos -98, 1872)
Keywords: 10.Cover Damage; 2.Damage; Condition: Fair; Hard Cover; Literature

Oeures Completes de Saint Augustin - Raulx, De M. L'Abbe (L. Guerin and C, Editeurs, 1872)
Keywords: 1.Conservation 保護; 15.Stain 污漬; 18.Bookworm; 2.Damage

Oeures Completes de Saint Augustin - Raulx, De M. L'Abbe (L. Guerin and C, Editeurs, 1872)
Keywords: 1.Conservation 保護; 15.Stain 污漬; 18.Bookworm; 2.Damage

Oeures Completes de Saint Augustin - Raulx, De M. L'Abbe (L. Guerin and C, Editeurs, 1872)
Keywords: 1.Conservation 保護; 15.Stain 污漬; 18.Bookworm; 2.Damage

Flores a Maria ou O Omes de Maio - Silva, Pe. Marthinho A. Pereira Da (1872)
Keywords: 1.Conservation 保護; 10.Cover Damage; 2.Damage

Compendio de Theologia Moral de S. Affonso Maria De Liguori - Vicoso, Antonio Ferreira (B. L. Garnier, 1872)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 10.Cover Damage; 18.Bookworm

Petite Histoire Grecque - Victor Duruy (Librairie Hachette et Cie, 1872)
Keywords: Condition: Fair; Hard Cover